Expansion microscopy in Placozoa: improving resolution and preservation of fragile samples during marine expedition - Romanova, Daria Y.; Frank, Yana A.; Moroz, Leonid L. (Frontiers in Marine Science, 2025)
Placozoa are small disc-shaped animals representing one of the early branching metazoan lineages with only a dozen cell types, fast effector reactions, and complex behaviors. The simplest organization and small cell sizes limit standard microscopy applications. Here, we implement a new methodology and protocol for expansion microscopy, improving both the resolution and preservation of fragile placozoans and kin. As a result, the proposed approaches can be applicable to a diversity of microscopic animals and their larvae with broad applicability for both laboratory and cross-disciplinary field research during long-term marine expeditions.